Increased left atrial stiffness in patients with atrial fibrillation detected by left atrial speckle tracking echocardio - Hatem abdel Rahman; Ayman K.M. Hassan; Ahmed H.S. Abosetta; Yehia T. Kishk (The Egyptian Heart Journal, 2015)
Objective: This study was designed to determine the contribution of left atrial (LA) stiffness to atrial fibrillation (AF) progression by comparing AF patients with normal control subjects, and to evaluate whether LA mechanical function is related to the structural changes of LA. Background: Abnormalities in the LA structure and function usually develop in patients with AF. Patients and methods: Twenty paroxysmal and 20 persistent AF patients, were included and studied, using standard, tissue Doppler and speckle tracking echocardiography, and were compared with 20 matched controls. LA maximal volume, mitral annular velocities, and global longitudinal LA strain were measured. The ratio of E/e′ to LA strain was used as an index of LA stiffness. Results: Study groups were comparable. Paroxysmal and persistent AF patients showed increased LA maximal volume (24.3 ± 3.2, 20.1 ± 5.2 vs. 18.3 ± 1.6, p < 0.001) and LV filling pressure (E/e′ = 9.5 ± 1.1, 7.9 ± 1.2 vs. 6.8 ± 1.1, p < 0.001), but decreased mitral annular velocities and LA strain (18.1 ± 2.8, 21.5 ± 4.3 vs. 25.9 ± 2.9, p < 0.001). LA stiffness was increased in patients with persistent and paroxysmal AF than in the control subjects (0.55 ± 0.12, 0.36 ± 0.09 vs. 0.26 ± 0.02, p < 0.001), and was related with LA diameter and LV filling pressure. Conclusions: Patients with AF have increased LA stiffness in comparison with that of the control subjects and it is higher in persistent than paroxysmal AF. LA volume and LV filling pressure are independent predictors of LA stiffness.